Application value of elbow arthrography in the treatment of chronic radial head dislocation in children - Jiang, Hai; Li, Tao (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate and analyze the application value of elbow arthrography in the treatment of chronic radial head dislocation in children.MethodsFrom January 2014 to January 2017, 15 children with chronic anterior radial head dislocation were treated (11 boys, 4 girls; average age 9 years, range 3–11 years). Intraoperative elbow arthrography was performed to assess the position of the radial head relative to the joint capsule. The nature of the dislocation was confirmed by opening the joint capsule to directly observe the relationship between the radial head and capitellum, as well as the morphology of the radial head. Reduction of the radial head was achieved via proximal ulnar osteotomy, and fixation was performed using a plate and screws with or without Kirschner wires (K-wires).ResultsElbow arthrography showed the radial head was located within the joint capsule in 12 cases and outside the capsule in 3 cases. Among the cases: All 8 congenital dislocations had the radial head within the joint capsule. Of the 7 traumatic dislocations, 4 had the radial head within the capsule and 3 outside. Direct inspection after capsulotomy confirmed the arthrography findings and revealed characteristic morphological differences. In congenital dislocations, there was no scar tissue between the radial head and capitellum, and the radial head fovea was shallow and flat. In traumatic dislocations, obvious scar tissue was present between the radial head and capitellum, and the radial head fovea was distinct. Three patients with traumatic dislocations (all with the radial head outside the capsule on arthrogram) required supplemental trans-articular K-wire fixation due to instability after reduction. Follow-up ranged from 9 months to 4 years (average 2 years 5 months). Postoperative radiographs showed no cases of radial head re-dislocation or subluxation. Postoperative elbow range of motion improved in all patients, with no reports of pain or functional instability.ConclusionElbow arthrography serves as a valuable adjunct for differentiating between congenital and traumatic radial head dislocations, thereby informing both surgical strategy and the decision for supplemental fixation. When stable bony alignment is achieved, proximal ulnar osteotomy without annular ligament reconstruction represents an effective management strategy for chronic radial head dislocation in children.